RESEARCH OF MARRIAGE AND DIVORCE PROCESSES FROM A SOCIAL-DEMOGRAPHIC ASPECT - Djumabayeva Shaira Xalillayevna (Western European Studies, 2024)
In this article, marriage and annulment of marriage, that is, divorce as a demographic process in Uzbekistan are studied from a scientific point of view. Laws on the structure of marriage, the age of marriage for young men and women have been studied. The changes in the absolute number and coefficient of registered marriages and divorces are analyzed. Regions with the highest rates of marriage and divorce, age-sex groups of married and divorced people and changes in it were studied. Divorcees compared to recorded marriages, divorces by number of children, divorces by duration of marriage, average age of divorcees, reasons for divorce and factors leading to divorce are studied based on the results of sociological research, conclusion and suggestion and recommendations are given
Keywords: marriage; annulment of marriage; divorce; group